(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To analyze the relationship between certain biochemical markers and the Albumin-Globulin Score (AGS). Subject and method: This descriptive analytical study was conducted on 98 newly diagnosed multiple myeloma (MM) patients from 2022 to 2024 at the National Institute of Hematology and Blood Transfusion. Results: The study population had a mean age of 64.7 years, with 44.9% being male. There were no statistically significant differences in age or gender across the different AGS groups. Albumin levels showed a decreasing trend as AGS increased (from 41.5 to 27.8), while globulin levels increased significantly from 29.2 to 90.5 with higher AGS scores (p < 0.05). Levels of β2-microglobulin (β2M), creatinine, calcium, and lactate dehydrogenase (LDH) did not differ significantly across AGS groups. The multivariate regression model for biochemical markers did not achieve statistical significance. Conclusion: There was no significant association between age, gender and AGS. Albumin was inversely correlated, while globulin was directly correlated with AGS. Levels of β2M, creatinine, calcium, and LDH were consistent across AGS groups.